Suppression of secondary hyperparathyroidism in uraemia: acute and chronic studies. Issue 6412 (21st January 1984) - Muirhead, N; Catto, G R; Edward, N; Adami, S; Manning, R M; O'Riordan, J L
Abstract : A study was conducted evaluating the response of serum parathyroid hormone to acute hypercalcaemia and long term administration of 1, 25-dihydroxyvitamin D3 (1, 25(OH)2D3) in patients receiving maintenance haemodialysis. During infusion of elemental calcium 4 mg/kg/h over four hours in 12 patients not receiving vitamin D the concentration of serum amino terminal parathyroid hormone fell by 31-96% (mean 74.8 (SD 17.6)%) while that of carboxy terminal parathyroid hormone changed little. There was a strong inverse correlation between baseline serum calcium concentration and percentage fall in amino terminal parathyroid hormone during infusion (r = 0.88; p less than 0.001). In seven patients who received prolonged treatment with 1, 25(OH)2D3 after calcium infusion there was a positive correlation between maximum percentage fall in amino terminal parathyroid hormone during infusion and the percentage fall in amino terminal parathyroid hormone after 1, 25(OH)2D3 treatment (r = 0.79; p less than 0.05). The responsiveness of the parathyroid glands to changes in calcium in acute studies may be used to predict the efficacy of long term treatment with 1, 25(OH)2D3. Patients in whom calcium infusion does not suppress parathyroid hormone may have true parathyroid autonomy and require early parathyroidectomy.